Chemometrics statistics and computer application in analytical chemistry - Otto, Matthias 1950- (Wiley-VCH, 2024)
Explore chemometrics from basic statistics to the latest artificial intelligence and neural network developments in this new edition Chemometrics is an area of study combining chemistry and mathematics. It governs the interpretation of data generated by chemical analysis, and its growth as a subfield promises to streamline and revolutionize analytical chemistry. Chemometrics has long been the leading introductory textbook in this subject. Beginning with an introduction to the statistical-mathematical evaluation of chemical measurements, it leads readers through modern chemometric approaches in a pedagogically sound and highly readable style. Now fully updated to reflect the latest research and applications of this exciting discipline, it provides essential tools for a new generation of analytical chemists. Readers of the fourth edition of Chemometrics will also find: New or expanded treatment of subjects such as deep learning, ANNOVA simultaneous component analysis, instrumental data output, and more Detailed discussion of approaches to signal processing, design and optimization of experiments, pattern recognition and classification, and many other areas Balance of theoretical and practical knowledge to enable rapid application of key techniques Chemometrics is ideal for advanced students in chemistry, analytical chemistry, pharmaceutical chemistry, biochemistry, or related subjects, and as a useful reference for practicing researchers and laboratory professionals.
Keywords: Chemometrie; Analytische Chemie; Analytical Chemistry; Biostatistics; Biostatistik; CH10: Analytische Chemie; CH30: Technische u. Industrielle Chemie; Chemie; Chemische Analyse; Chemistry; Chemometrik; Computational Chemistry u. Molecular Modeling; Industrial Chemistry; ST30: Biostatistik; Statistics; Statistik; Technische u. Industrielle Chemie; Umweltchemie